2017
DOI: 10.2141/jpsa.0150181
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Boron and Phytase, Alone or in Combination, in Broiler Diets

Abstract: A total of 800 day-old broiler chicks were assigned to four test diets to assess the efficacy of phytase, fermented from Aspergillus niger, and boron, as boric acid, on the growth performance and mineral profile in chickens. The dietary treatments included the basal diet and the basal diet supplemented with boron (20 mg/kg), phytase (500 phytase units/kg diet), or a combination of boron and phytase. The following parameters were measured: growth performance indices, serum biochemicals, ash and the mineral prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Boron supplementation within the diet (240 ppm, 0.024%) was not detrimental to broiler performance when administered from day-of-hatch to 21 D, although boron levels within breast muscle and liver tissues increased in proportion to boron dietary concentration ( Rossi et al., 1993 ). Boron (20 mg/kg) supplementation in a basal diet had no impact on body weight or feed consumption in chickens; results did not suggest growth promotion or metabolic mineral regulation ( Küçükyilmaz et al., 2017 ). However, the acute oral mean lethal dose of BA in 1-day-old chicks was determined to be 2.95 ± 0.35 g/kg of body weight, resulting in the classification as a slightly toxic chemical ( Sander et al., 1991 ).…”
Section: Introductionmentioning
confidence: 91%
“…Boron supplementation within the diet (240 ppm, 0.024%) was not detrimental to broiler performance when administered from day-of-hatch to 21 D, although boron levels within breast muscle and liver tissues increased in proportion to boron dietary concentration ( Rossi et al., 1993 ). Boron (20 mg/kg) supplementation in a basal diet had no impact on body weight or feed consumption in chickens; results did not suggest growth promotion or metabolic mineral regulation ( Küçükyilmaz et al., 2017 ). However, the acute oral mean lethal dose of BA in 1-day-old chicks was determined to be 2.95 ± 0.35 g/kg of body weight, resulting in the classification as a slightly toxic chemical ( Sander et al., 1991 ).…”
Section: Introductionmentioning
confidence: 91%
“…The increase of minerals in plasma was attributed to the interaction of B with macroelements (Ca, P,Mg), thereby modifying their concentration in the plasma of chickens (Kurtoglu et al, 2001(Kurtoglu et al, , 2005Bozkurt et al, 2012). Moreover, Kucukyilmaz et al (2017) confirmed that the addition of B to the diet resulted in significant increase in B concentration of serum. In contrast, Kaya and Macit (2018) reported that B supplementation did not change serum P and Mg level, while decreased serum Ca content in laying hens.…”
Section: Mineral Content In Serum Bone Muscle and Livermentioning
confidence: 65%
“…The contradictory results of these studies are difficult to evaluate because of the different protocols used, including differences in breed, their level of performance, differences in the composition and nutritive value of the diets, different source and form of boron supplementation, including inherent boron concentrations in the basal diet. Birds receiving a diet with supplemental boron excreted more iron (Kucukyilmaz et al, 2017;Pradhan et al, 2020) and manganese (Pradhan et al, 2020). The decreased femur iron concentration may be the reflection of its higher excretion.…”
Section: Resultsmentioning
confidence: 99%
“…For poultry, 2 ppm of B was recommended by NRC (1984) but this recommendation has not been made in the latest feeding standards for poultry (NRC, 1994;ICAR, 2013). Dietary B supplementation has been reported to improve the performances of broiler (Pradhan et al, 2020;Bozkurt et al, 2012;Kucukyilmaz et al, 2017) in terms of body weight gain, feed intake and feed conversion ratio. Moreover, supplemental B improve bone calcium content in rat (Nielsen, 2004), laying hens (Mizrak et al, 2010) and broiler (Bozkurt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%